CmBGI Gene Expression encoding β-glucosidase in melon (Cucumis melo L.) under stress condition - Yuanita Rachmawati; Ganies Rizaa Aristya; Budi Setiadi Daryono (Program Studi Biologi, Fakultas Sains dan Teknologi, Universitas Islam Negeri Sunan Ampel Surabaya, 2017)
CmBGI is the enzymatic genes encoding β-glucosidase that involved in Abscisic Acid (ABA) metabolism of Cucumis melo L. β-glucosidase promotes the accumulation of glucose, fructose, and sucrose, and it might act as a regulator that mediates melon fruit ripening both climacteric and nonclimacteric. ABA mediates adaptive responses to abiotic and biotic stresses. Agricultural Balitbang in 1997 showed that there were approximately 158.600 ha of degraded land scattered in three zones of agroecosystems in Yogyakarta (DIY). One of them is Dlingo Bantul area which has a karst type critical land area. Karst provides stress to the certain plant growth. One way to conserve critical land is making this area for agriculture. Cultivar TACAPA and TA were superior melons that have been developed by Genetic Laboratory of Biology Faculty UGM. This preliminary research was conducted to examine molecular characterization of CmBGI gene expression in cultivar TACAPA and TA which are planted in normal condition medium and in critical land medium treatment. Total RNA was extracted from leaf tissue then Reversed Transcriptase (RT-PCR) to collect cDNA library. cDNA was amplified using specific primer. Spectrophotometry was conducted in λ260 nm and electrophoresis run in 1.5% agarose gel. Control of band chosen was Cm-Actin. CmBGI gene concentration of TACAPA and TA in normal condition medium are in succession 578.5 and 579.4 μg/ml then for critical land medium treatment 743.4 and 773.5 μg/ml. CmBGI band was showed both of TACAPA and TA as ± 1258 bp. Cm-actin was showed band of DNA as ± 445 bp. CmBGI gene concentration in critical land medium treatment which is given greater stress on melons are higher than normal condition. This suggests that the CmBGI gene is expressed more in cultivar TACAPA and TA melons when they are grown under stress condition.